Modeled Substitution of Traditional Oils with High–Oleic Acid Oils Decreases Essential Fatty Acid Intake in Children. Issue 4 (15th December 2021) - Belury, Martha A; Raatz, Susan; Conrad, Zach
ABSTRACT: Background: High–oleic acid (OA) vegetable oils are replacing some traditional vegetable oils in the US food supply. This may lead to reduced intake of the essential fatty acids (EFAs) linoleic acid (18:2n-6) and α-linolenic acid (18:3n-3) in children, who need EFAs for growth and development and reduced risk for cardiometabolic disease into adulthood. Objectives: The objectives of this study were the following: 1 ) to estimate trends in daily intake of EFAs among children aged 1–8 y, 2 ) identify top food sources of EFAs, and 3 ) evaluate the effects of replacing traditional oils with high-OA oils on meeting daily recommended intakes of EFAs. Methods: Dietary data from 7814 children aged 1–8 y were acquired from the NHANES (2007–2016). Using a diet model, we evaluated the effect of replacing 20%, 40%, 60%, and 80% of traditional oils with high-OA oils on meeting adequate intakes (AIs) for EFAs. Results: Major food sources of EFAs among all age–sex groups were grain dishes (35–40% of daily intake), meat and seafood dishes (17–21%), and fruit and vegetable dishes (12–14%). Replacing 40% or more of traditional oils with high-OA oil varieties will lead to inadequate daily intakes of EFAs. Conclusion: Replacement of traditional vegetable oils with high-OA varieties will place children at risk of not meeting the AI levels for EFAs. A balanced approach of including traditional oils and high-OA oils in the US food supply is needed to prevent inadequate intakes of EFAs in children. Graphical Abstract: